Vysetrení kondenzátu vydechovaného vzduchu u cystické fibrózy - Fila, Libor; Musil, Jaromír (Casopis lekaru ceskych, 2010)
Examination of exhaled breath condensate belongs to experimental methods that are used in many pulmonary diseases and it can take part in the study of their pathophysiology. Its contribution to diagnostics and to monitoring of response to treatment is also evaluated. Many biomarkers of inflammation and oxidative stress were studied in exhaled breath condensate in cystic fibrosis. Examination of pH of exhaled breath condensate is considered to be useful in evaluation of inflammatory acidification of airways, together with evaluation of response to antibiotic treatment of pulmonary exacerbation, due to immediately accessible result. Other important biomarkers include 8-isoprostane and 3-nitrotyrosine as markers of oxidative stress (both with negative correlation with pulmonary function) and leukotriene B4 as marker of neutrophilic inflammation. Opposite to other pulmonary diseases, hydrogen peroxide does not belong to useful markers of oxidative stress in cystic fibrosis, due to abundant reduced thiols and glutathione peroxidase in sputum of these patients. Attempts to detect bacterial DNA in exhaled breath condensate in cystic fibrosis also failed. In spite of mentioned progress, examination of exhaled breath condensate remains a research method and it has not been introduced into clinical practice.
Keywords: Breath Tests; Biomarkers; Cystic Fibrosis; biologické markery; lidé; cystická fibróza; Humans; dechové testy